Penggabungan Metode Vigènere Cipher dan ElGamal Pada Pengamanan Pesan Rahasia - Ludyawati, Ludyawati; Khudzaifah, Muhammad; Herawati, erna (Jurnal Riset Mahasiswa Matematika, 2023)
Vigènere Cipher is a symmetric cryptographic algorithm that uses the same type of key in the encryption and decryption process. The security of the Vigènere Cipher method lies in the modulo calculation used. ElGamal is an asymmetric cryptographic algorithm that uses two different types of keys in the encryption and decryption process. The security of the ElGamal algorithm lies in the complexity of calculating large prime numbers. The Vigènere Cipher and ElGamal have their advantages and disadvantages. The researchers are interested in combining the advantages of the two methods. In this study, two locks were carried out in the encryption and decryption process. The encryption process uses a public key and the decryption process uses a public key  and a secret key . The key used comes from key formation using the ElGamal algorithm. The key security formed from the ElGamal algorithm lies in the large prime , the primitive root  of the prime number , and the random integer  which comes from the last three digits of Student Number. The conclusion of this study is that the combination of the Vigènere Cipher and ElGamal methods can increase the security of  secret messages because it produces a ciphertext with twice the size ) of  the original message.